Prachāk̨̄on Thai samai R̨̄o. 9 : nangs̄ư wichākān n̄ưang nai ʻōkāt phrarātchaphithī mahāmongkhon chal̄œm phrachonmaphansā 6 r̨̄op, 5 Thanwākhom 2542 - Bunl̄œt Līeopraphai; Bhumibol Adulyadej, King of Thailand, 1927- (Sathāban Wičhai Prachāk̨̄on læ Sangkhom, Mahāwitthayālai Mahidon, 1999)
On Thai population in the reign of Bhumibol Adulyadej, King of Thailand, b. 1927; volume commemorating his 72nd Birth anniversary, December 5, 1999.